Peptides from the croceine croaker (Larimichthys crocea) swim bladder attenuate busulfan-induced oligoasthenospermia in mice - Xi Zhao; Mengmeng Sang; Ping Han; Jie Gao; Zhenhua Liu; Hu Li; Yayun Gu; Chengniu Wang; Fei Sun (Taylor & Francis Group, 2022)
Context The swim bladder of the croceine croaker is believed to have a therapeutic effect on various diseases. However, there is no research about its effect on mammalian spermatogenesis. Objective We investigated the swim bladder peptides (SBPs) effect on busulfan-induced oligoasthenospermia in mice. Materials and methods We first extracted SBP from protein hydrolysate of the croceine croaker swim bladder, and then five groups of ICR male mice were randomly assigned: control, control + SBP 60 mg/kg, busulfan, busulfan + SBP 30 mg/kg and busulfan + SBP 60 mg/kg. Mice received bilateral intratesticular injections of busulfan to establish oligoasthenospermia model. After treatment with SBP for 4 weeks, testis and epididymis were collected from all mice for further analysis. Results After treatment with SBP 30-60 mg/kg for 4 weeks, epididymal sperm concentration and motility increased by 3.9-9.6- and 1.9-2.4-fold than those of oligoasthenospermia mice induced by busulfan. Meanwhile, histology showed that spermatogenic cells decreased, leading to increased lumen diameters and vacuolization in the busulfan group. These features were reversed by SBP treatment. RNA-sequencing analysis revealed that, compared with the busulfan group, Lin28b and Igf2bp1 expression related to germ cell proliferation, increased with a >1.5-fold change after SBP treatment. Additionally, PGK2 and Cfap69 mRNAs associated with sperm motility, also increased with a >1.5-fold change. Furthermore, these findings were validated by quantitative real-time PCR and Western blotting. Discussion and conclusions This is the first reported evidence for the therapeutic effect of SBP on oligoasthenospermia. SBP may be a promising drug for oligoasthenospermia in humans.